KAJIAN KETERSEDIAAN KAYU BAKAR PADA PENGRAJIN GULA MERAH - Tjutju Nurhayati; Wesman Endom; Dadan Dadan (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
A survey pertaining to the topic as such has been conducted in three particular locations, where the sugar industries that consume fuel wood were situated, i.e. Jasinga (West Java), Gombong (East Java). and Karangasem (Bali). The inherent data were collected using the cluster-plot method to figure out the potential of available firewood in the community land. The main data covered the amount of organic foliage debris (i.e. twigs, small branches, etc.) which fall off the tree stands naturally, the potential volume of stands, and their regeneration rate to provide a reserve fuel wood which can be available whenever ii is needed. Meanwhile, the supplementary data were the firewood consumption, cooking stove efficiency, palm-sugar production, and palm-sugar yield and qualities, which in all were obtained through a trial observation in the field.The results revealed that the availabilities of foliage debris (biomass wastes) that fell-off to thetree base (ground) and of firewood from the branch-free portions of the upper tree stands, in percentage of the amount required by the industries, were consecutively 0.20- and 0.61-%ha (Karangasem), 0.02- and 0.63-%/ha (Gombong), and 4. 78- and 1. 17-%/ha (Jasinga). With respect to the area, Karang asam and Jasinga showed adequate availability of biomass wastes, but lack of firewood occurred in Gombong since the available stock was only around 70 %. Such high consumption of firewood was due to the fact that there were about 7160 palm-sugar industries in Gombong, while in Karangasem and Jasinga were only 550 and 65 industries. respectively.The highest consumption offirewood-derived energy was in Jasinga (219.33 GJ/m3), followed in decreasing order, i.e. 198.00 GJ/m3 in Gombong and l44.44 GJ/m3(as the lowest) in Karangasem. The high-energy consumption in Jasinga was brought about by the use of low-efficiency stove (i.e. 15. 07 %). Meanwhile, the efficiencies of the ones in Combong and Karangasem were significantly higher, i.e. 18. 62 and 30.12 percent, respectively. The consumptions of firewood per household per year in such three locations were 2100 kg (Karangasem), 3924 kg (Gombong). and Jasinga (3456 kg).The highest yield (recovery) of palm sugar was obtained from the cooking of arenga juice (55.56%), while the lowest from palm juice (8. 77 %). About the qualities, based on the results of chemical analysis which covered the carbohydrate, water, ash, P. Ca, and Fe, and calorific values, the palm sugar from lontar juice was regarded as the best.followed by the ones from palm and arenga juices. One way to cope with the continual consumption of firewood was through the planting of tree species which are able to produce high-energy firewood and take short-rotation growth periods, such as kaliandra, lamtoro, and sengon. As such, the minimum area of the planting sites, as an example.for lamtoro should be 178 ha (in Karangasem), 4494 ha (Gombong), and 37 ha (Jasinga).